Multi-Path Tcp In Vehicular Ad-Hoc Networks (Vanets) - Sura Kadhum ABED; Asst. Prof. Dr. Didem KIVANÇ TÜRELİ (Genius Journals, 2024)
Vehicular ad hoc networks (VANETs) have an important role in the next generation of vehicular technology. The VANETs goals are to provide drivers and other users on the road with superior benefits such as improved safety, traffic management, and other related information, by combining information and communication technology into transportation infrastructure. A more effectient VANET routing protocol must be designed as a result. Conventional engineering of the network forces a specific communication solution execution. Due to regular TCP limitations, go-to transport protocols for (VANETs) are an efficient solutions. Nevertheless, it is well know one of the main drowbacks of regular TCP protocol is the communication reliability in congestion situations thar attribute packet losses. VANETs are characterized by high vehicular speeds and rabid (disconnect/reconnect) environments, both of which can cause frequent network disruptions. Degrading the performance of the network is unnecessary, as is a reduction in data rate and similar behavior. This paper will showcase and investigate this issue using ns-3 simulations and compare the behavior of the regular TCP against Multi-Path TCP using a group of vehicles in scenarios involving direct communication and relay points with various distances. Our study goal is to improve the behavior of regular TCP protocales using MPTCP. This is done by providing a clear evaluation of network performance in such reoccurring disturbances
Keywords: Vehicular ad hoc networks; Transmission Control Protocol